Chinese classics stories to awaken the world - Feng Menglong (Chinese classics stories, 2017)
San Yan refers to the three short story collections of the Ming Dynasty written by Feng Menglong: Instruction Stories to Enlighten the World, Stories Enlightening the World, and Stories to Awaken the World. The three books consist altogether of 120 pieces with each composed of 40. Rich in content, San Yan deals with almost every aspect of the social life of the time and reflects the characteristics of the era which witnessed the decline of the feudal lord class and the gradual rise of the townsfolk stratum. San Yan represents the summit of ancient short story writing in vernacular Chinese. This book is edited and translated by the famous translator Wang Guozhen, to introduce Stories to Awaken the World the World to the foreign readers.